Heteropoda schwendingeri Jäger 2005 (Araneae: Sparassidae) — first description of female with notes on intraspecific variation and evidences supporting species status - Eusemann, Pascal; Jäger, Peter (Zootaxa, 2006)
The female of Heteropoda schwendingeri Jäger 2005 is described for the first time. Notes on intraspecific variation are given from two males and three females from the type locality, Than Lod Yai cave. Small variation and consistent combination of both male and female characters confirm its species status.